Maintaining remission in granulomatosis with polyangiitis (Wegener's). (October 2012) - Reinhold-Keller, Eva; Moosig, Frank
Since the introduction of combined immunosuppressive therapy with oral cyclophosphamide (CYC) and glucocorticosteroids in the 1970s, the outcome of antineutrophil cytoplasmic antibody-associated vasculitides, for example, in granulomatosis with polyangiitis (Wegener`s), improved dramatically. However, the long-term follow-up of patients treated with CYC plus glucocorticosteroids has revealed high treatment-related morbidity and mortality and a high relapse rate (up to 50%), often re-requiring CYC and glucocorticosteroids. Today, according to the European League Against Rheumatism recommendations for the management of small- and medium-vessel vasculitis, the treatment paradigm for severe courses of granulomatosis with polyangiitis consists of CYC for the induction of remission, followed by a less-toxic maintenance therapy for the prevention of relapses. Azathioprine, methotrexate, leflunomide and mycophenolate mofetil proved efficacy for maintaining remission in randomized controlled trials. However, despite clear improvements achieved by the use of maintenance strategies, frequent relapses are still a major concern in the care for granulomatosis with polyangiitis patients, and reliable biomarkers indicating patients at risk of relapse are lacking. The question on the optimal duration of the treatment for remission maintenance has also not yet been answered.